Protocol for a Hybrid-type 1 pilot study of a randomized control trial of a brief, peer-delivered treatment to improve father depression and child mental health in Kenya - Ali Giusto; Florence Jaguga; Dan Aburi; Mercy Korir; Winnie Maina; Wilter Rono; Michaela Greenlee (PLoS ONE, 2025)
Background Few treatments specifically target father depression and alcohol use, despite their high prevalence worldwide and adverse impacts on families and youth. Fathers are also less likely to engage in treatment than female caregivers. To address this gap, a team of US- and Kenyan-based clinician-researchers developed Learn, Engage, Act, Dedicate (LEAD), a five-session, task-shifted psychosocial intervention for fathers in Eldoret, Kenya. Objective This hybrid type-1 study aims to evaluate the feasibility, acceptability, and preliminary effectiveness of LEAD, a peer-father delivered psychosocial intervention for fathers at risk for depression and alcohol use. Secondary aims include exploring changes in child mental health and family functioning, potential mechanisms of change, and key implementation outcomes such as fidelity. Methods We will conduct a hybrid type-1 pilot study using a parallel randomized controlled trial (RCT) design, enrolling 102 fathers randomized 2:1 to LEAD or a waitlist control group. All participants will be offered treatment as usual at baseline, with waitlist participants receiving LEAD following the waitlist period. Assessments will be conducted with fathers, their female partners, and one child aged 8–17. Primary aims are to explore changes in fathers’ depression and alcohol use; secondary aims include examining changes in family functioning and child well-being, understanding mechanisms driving change or nonresponse, and assessing the feasibility and acceptability of peer-father counselor implementation. Discussion Findings will inform a future hypothesis-testing hybrid trial to examine LEAD’s effectiveness in improving father and child mental health and evaluate associated implementation strategies. This work will contribute to strategies for engaging and retaining men in mental health services. Trial Registration #: NCT06489314 (ClinicalTrials.gov); July 4, 2024